PENGARUH INFUSA DAUN KELOR (Moringa oleifera) SEBAGAI PRESERVATIF ALAMI TERHADAP NILAI pH DAN TOTAL MIKROBA DAGING BROILER - Hari, Putu Gaura; Wanniatie, Veronica; Ermawati, Ratna; Riyanti, Rr (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2025)
Moringa oleifera are one of the antimicrobial plants because the content of tannins, flavonoids, and alkaloids in moringa leaves can act as antibacterials that can be used as natural preservatives. This study aims to determine the effect of moringa leaf infusion on (pH value and Total microbes) This study is an experimental study using a completely randomized design (CRD) with 4 treatments and 5 replications and infusion concentrations P0 (without marinating), P1 (5%), P2 (10%) and P3 (15%). The variables observed were the pH value and total microbes which would be analyzed quantitatively using ANOVA and the BNT test at a further test level of 5%, the best decrease in pH value and number of bacteria was shown in P3, namely broiler meat soaked in moringa leaf infusion with an infusion concentration of 15%.